The Role of Faith-Based Organizations in Maternal and Newborn Health Care in Africa - Widmer, M.; Betran, A. P.; Merialdi, M.; Requejo, J.; Karpf, T. (2012)
BACKGROUND: Global disparities in maternal and newborn health represent one of the starkest health inequities of our times. Faith-based organizations (FBOs) have historically played an important role in providing maternal/newborn health services in African countries. However, the contribution of FBOs in service delivery is insufficiently recognized and mapped. OBJECTIVES: A systematic review of the literature to assess available evidence on the role of FBOs in the area of maternal/newborn health care in Africa. SEARCH STRATEGY: MEDLINE and EMBASE were searched for articles published between 1989 and 2009 on maternal/newborn health and FBOs in Africa. RESULTS: Six articles met the criteria for inclusion. These articles provided information on 6 different African countries. Maternal/newborn health services provided by FBOs were similar to those offered by governments, but the quality of care received and the satisfaction were reported to be better. CONCLUSION: Efforts to document and analyze the contribution of FBOs in maternal/newborn health are necessary to increase the recognition of FBOs and to establish stronger partnerships with them in Africa as an untapped route to achieving Millennium Development Goals 4 and 5.